PENCIPTAAN BATIK Korporat Isi surakarta - Sukirno, S (Institut Seni Indoensia Surakarta, 2018)
This research on arts creation focuses on creation of corporate batik for InstitutSeni Indonesia Surakarta. The created model is possible to be applied to other institution. The creation of batik corporate is based on the need of a uniform for institution unity as well as to express good image to the community. This research applies the approach of design creation implemented in the series of batik creation especially of Institut Seni Indonesia. The research method of design creation includes the following steps: (1) identification (2) research (3) formulating ideas (4) prototype (5) selection (6) application (7) evaluation. The result represents the specific batik of Institut Seni Indonesia Surakarta academic staffs according to institution vision. The vision and mission of Institution can be searched from the realized logo and the official color of Institution as well as landscape that can become the icon.Keywords: Batik, corporate, ISI Surakarta